JUDGE’S DISCRETION IN ISLAMIC FAMILY LAW: INDONESIAN RELIGIOUS COURTS EXPERIENCE - Wahyudi, Muhamad Isna (Jurnal Hukum dan Peradilan, 2014)
Tension between Islamic legal tradition and the modern nation state’s role in establishing dan reforming law has become the global controversies and conflicts in Muslim countries over the last decades including Indonesia. Since the enactment of Law No.1/1974 on Marriage, then Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) under President Instruction No.1/1991, dualism of the validity of marriage has been arising in Indonesian Muslim society. The dualism has led to ambivalence towards law enforcement among judges of religious courts in dealing with the petitions for the legalization of marriage while the Law restricts the petitions to marriages before the enactment of Law No.1/1974. In this case, judges of religious court have deviated from the state law by granting legalization to marriages occurred after the enactment of Law No.1/1974. Such deviation is known as judge’s discretion. Despite judges of religious courts seem to adhere to the Islamic legal tradition than the State law in the case of legalization of marriage; they have deviated from Islamic legal tradition or state law in terms of the fulfillment of divorced wife’s rights, joint property, custody, and inheritance. Their discretion is merely to provide the justice to the litigants when the application the letter of the law is contradictory to justice. In this way, they have also taken a part in reforming the Islamic FamilyLaw.Keywords: judge, discretion, justice.